Religiosity, happiness and suicidal behaviour: a cross-sectional comparative study in Iran. Issue 2 (7th February 2021) - Dadfar, Mahboubeh; Lester, David; Abdel-Khalek, Ahmed M.
ABSTRACT: A sample of 102 Iranian psychiatric outpatients was selected. For a comparison group, a sample of 72 Iranian university employees was recruited. Participants responded to the Self-Rating Scale for Religiosity and the Self-Rating Scale of Happiness, and the Suicidal Behaviour Questionnaire-Revised. The correlations of religiosity and happiness with suicidal behaviour for the patients were negative and significant, but the employees were negative and non-significant. The correlations between religiosity and happiness scores for the patients were positive and significant, but the employees were non-significant. Patients obtained significant lower scores for religiosity and happiness than did employees, and higher scores for suicidal behaviour. Sex differences in the scale scores were not significant for the patients, but male employees obtained significant higher scores for religiosity than did females. Religiosity may have a positive impact on the happiness of psychiatric patients and on their suicidal behaviour, indicating that encouraging religious activities for psychiatric patients may improve their subjective well-being.